Downregulation of metabotropic glutamate receptor 5 alleviates central sensitization by activating autophagy via inhibiting mTOR pathway in a rat model of chronic migraine. (19th January 2021) - Niu, Yingying; Zeng, Xiaoxu; Qin, Guangcheng; Zhang, Dunke; Zhou, Jiying; Chen, Lixue
Highlights: Metabotropic glutamate receptor 5(mGluR5) is upregulated in chronic migraine(CM). Downregulation of mGluR5 alleviated the allodynia and central sensitization. MGluR5 regulated autophagy by the mTOR pathway in CM. Autophagy was associated with the allodynia and inflammatory factor in CM. Abstract: Central sensitization is one of the important pathological mechanisms of chronic migraine (CM). Metabolic glutamate receptor 5 (mGluR5) mediates pain by activating various intracellular pathways. However, whether mGluR5 contributes to central sensitization in CM and the exact mechanism remains unclear. Male rats were used to establish a CM model by repeated infusions of inflammatory soup (IS) for 7 days to stimulate the activation of the dural nociceptor. The mechanical and thermal thresholds were used to evaluate allodynia, and central sensitization was assessed by measuring calcitonin gene-related peptide (CGRP) and substance P (SP). Microtubule associated protein 1 light chain 3 (LC3) and p62/SQSTM1 were used to assess autophagy. We found that the expression of mGluR5 in the trigeminal nucleus caudalis (TNC) of CM rats was significantly increased. In addition, the downregulation of mGluR5 activated autophagy by inhibiting the mTOR pathway. Moreover, the activation of autophagy alleviated allodynia and central sensitization in CM rats. This study identified a novel strategy for the treatment of CM; the downregulation of mGluR5 in a rat model of CM decreased the expression of the inflammatory factor interleukin-1 beta (IL-1β) and the central sensitization-associated proteins CGRP and SP by activating autophagy via inhibiting the mTOR pathway.